2017
DOI: 10.1039/c7cy00001d
|View full text |Cite
|
Sign up to set email alerts
|

DNA-supported palladium nanoparticles as a reusable catalyst for the copper- and ligand-free Sonogashira reaction

Abstract: DNA nanotechnology has recently emerged as a powerful discipline with diverse applications. However, studies focused on the combination of DNA and metal nanoparticles for catalyst design are scanty. We have prepared a catalyst composed of palladium nanoparticles supported on DNA which has been characterised by TEM, SEM, EDX, UV, FTIR and XPS. The catalyst, mainly composed of Pd(II) and Pd(IV) species in the form of oxides, has been effectual in the copper-and ligandfree Sonogashira-Hagihara coupling of aryl io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 80 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…According to the literature, the main catalytic active species for the coupling reactions is Pd . The proposed mechanism for the ligand‐ and copper‐free Sonogashira coupling reaction in the presence of the catalyst is as follows.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, the main catalytic active species for the coupling reactions is Pd . The proposed mechanism for the ligand‐ and copper‐free Sonogashira coupling reaction in the presence of the catalyst is as follows.…”
Section: Resultsmentioning
confidence: 99%
“…After the functionalization of MNPs with bis[3‐(triethoxysilyl)propyl]amine (Figure b), an additional prominent peak at 1027 cm −1 was observed for Si‐O bond stretching along with peaks for C‐H stretching at 2929 cm −1 and 2877 cm −1 , confirming silane functionalization. Apart from the peaks in the 3000–3500 cm −1 range which belongs to N‐H and C‐H stretching, the major peaks at 1695 cm −1 (C=O), 1657 cm −1 (C=N), and 1538 cm −1 (C=C) of DNA nucleobases and peaks at 1239 cm −1 (asymmetric PO 2 − stretching), 1060 cm −1 (symmetric PO 2 − stretching), and 963 cm −1 (P‐O‐C backbone stretching) were observed in the FT‐IR spectrum of DNA (Figure c). The successful incorporation of DNA onto SMNP can be understood from Figure d, wherein the peaks corresponding to both DNA and SMNP are present with a slight shift in the wavenumbers along with the disappearance of P‐O‐C backbone stretching at 963 cm −1 and some stretching and bending vibrations of groups in the nucleobases present which may be due to interaction with Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recycling experiments were conducted, but using a Suzuki coupling, observing a low decrease in the activity after ten runs and not significant palladium leaching. Moreover, even DNA has been used recently as a biopolymeric support for PdNPs, able to catalyze (0.5 mol%) the Sonogashira reaction between aryl iodides and aromatic and aliphatic terminal acetylenes [50]. The reaction is carried out in methanol as solvent at 65 • C, using cesium carbonate as base.…”
Section: Carbon-based Material-supported Palladium Catalystsmentioning
confidence: 99%
“…After recovering the catalyst by centrifugation, recycling experiments carried out in the coupling of iodobenzene and phenylacetylene shown that the supported PdNPs could be reused up to five times with some decrease in the performance in the fifth run, minor inactive palladium leaching being observed. catalyze (0.5 mol%) the Sonogashira reaction between aryl iodides and aromatic and aliphatic terminal acetylenes [50]. The reaction is carried out in methanol as solvent at 65 °C, using cesium carbonate as base.…”
Section: Carbon-based Material-supported Palladium Catalystsmentioning
confidence: 99%
See 1 more Smart Citation